Second-harmonic generation in the topological multifold semimetal RhSi - Baozhu Lu; Sharareh Sayyad; Miguel Ángel Sánchez-Martínez; Kaustuv Manna; Claudia Felser; Adolfo G. Grushin; Darius H. Torchinsky (Physical Review Research, 2022)
Recent experiments in the topological Weyl semimetal TaAs have observed record-breaking second-harmonic generation (SHG), a nonlinear optical response at 2ω generated by an incoming light source at ω. However, whether SHG is enhanced in topological semimetals in general is a challenging open question because their band structure entangles the contributions arising from trivial bands and topological band crossings. In this work, we circumvent this problem by studying RhSi, a chiral topological semimetal with a simple band structure with topological multifold fermions close to the Fermi energy. We measure SHG in a wide frequency window, ω∈[0.27,1.5]eV and, using first-principles calculations, we establish that, due to their linear dispersion, the contribution of multifold fermions to SHG is subdominant as compared with other regions in the Brillouin zone. Our calculations suggest that parts of the bands where the dispersion is relatively flat contribute significantly to SHG. As a whole, our results suggest avenues to enhance SHG responses.